VET Teachers’ and Schools’ Capacities to Tackle the Challenges of Vulnerable Students in the Baltic Countries and Norway - Tikkanen, Tarja; Tūtlys, Vidmantas; Vaitkutė, Lina; Kaminskienė, Lina; Ümarik, Meril; Loogma, Krista; Sloka, Biruta; Buligina, Ilze (Pedagogika, 2024)
This paper explores the institutional, organizational, and individual level capacities of VET teachers and schools in Estonia, Latvia, Lithuania, and Norway to support vulnerable students to help them to complete their education. Documents and secondary statistical analysis carried out in and across the four countries, revealed pronounced differences between Norway and the Baltic countries and across the latter. The implications of the findings are discussed within the analytical framework and the two models of skills formation.